APPLICATION OF SNOWBALL THROWING MODEL TO IMPROVE SOCIAL SCIENCE LEARNING OUTCOMES TO THE THEME OF HEAT AND ITS DISPLACEMENT ABOUT HUMAN INTERACTION WITH ENVIRONMENT IN FIFTH GRADE OF SD NEGERI 1 TAMBAKAGUNG IN THE ACADEMIC YEAR OF 2019/2020 - Zulhija Yanto; Ngatman Ngatman; Joharman Joharman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The objectives of the study were: (1) to describe the steps in application of snowball throwing model, (2) to improve social science learning outcomes about human interaction with the environment, and (3) to describe obstacles and solutions in the application of snowball throwing model. It was Collaborative Classroom Action Research (CAR). The data was in the form of quantitative and qualitative data. Data collection techniques used observation, interviews and tests. The results of this study were: 1) the steps in application of snowball throwing model were: (a) teacher conveyed material, (b) teacher divided students into groups and conveyed material, (c) group leader conveyed material to group members, (d) teacher asked the students to write questions in worksheets, (e) the students made a ball from paper containing questions and threw it to another group, (f) student received the ball and answered the questions alternately, and (g) teacher evaluated and made closing; 2) the application of snowball throwing model improved social science learning outcomes about human interaction with environment; (3) the obstacle was that the  students were passive in giving response to the result of discussion and the solution was giving rewards to the students who gave response so that they were more motivated.